2019
DOI: 10.3390/cancers11121833
|View full text |Cite
|
Sign up to set email alerts
|

JAK/STAT-Activating Genomic Alterations Are a Hallmark of T-PLL

Abstract: T-cell prolymphocytic leukemia (T-PLL) is a rare and poor-prognostic mature T-cell leukemia. Recent studies detected genomic aberrations affecting JAK and STAT genes in T-PLL. Due to the limited number of primary patient samples available, genomic analyses of the JAK/STAT pathway have been performed in rather small cohorts. Therefore, we conducted-via a primary-data based pipeline-a meta-analysis that re-evaluated the genomic landscape of T-PLL. It included all available data sets with sequence information on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 53 publications
1
52
0
Order By: Relevance
“…Phospho-STAT5 was shown to play a key role in CD34+/CD38− myeloproliferative neoplasms with downregulation by pharmacologic inhibition of JAK and STAT [24]. JAK/STAT mutations were also identified in patients with the rare and aggressive T-cell prolymphocytic leukemia (T-PLL), pointing towards a possible mode of transformation [25]. Additionally, STAT3 (and not STAT5B) mutations were identified in multiple peripheral T-cell lymphomas (PTCL), as well as high pY-STAT3 expression, particularly in angioimmunoblastic T-cell lymphoma (AITL) and anaplastic large cell lymphoma (ALCL) patient samples, two different PTCL cancer types [26].…”
Section: Chapter 1: Targeting Stat3/5 In Hematopoietic Cancersmentioning
confidence: 99%
“…Phospho-STAT5 was shown to play a key role in CD34+/CD38− myeloproliferative neoplasms with downregulation by pharmacologic inhibition of JAK and STAT [24]. JAK/STAT mutations were also identified in patients with the rare and aggressive T-cell prolymphocytic leukemia (T-PLL), pointing towards a possible mode of transformation [25]. Additionally, STAT3 (and not STAT5B) mutations were identified in multiple peripheral T-cell lymphomas (PTCL), as well as high pY-STAT3 expression, particularly in angioimmunoblastic T-cell lymphoma (AITL) and anaplastic large cell lymphoma (ALCL) patient samples, two different PTCL cancer types [26].…”
Section: Chapter 1: Targeting Stat3/5 In Hematopoietic Cancersmentioning
confidence: 99%
“…1,11 Activating lesions in janus kinase (JAK) and signal transducer and activator of transcription (STAT) molecules as well as epigenetic aberrations have emerged as further hallmarks of T-PLL pathology, resulting in a sustained survival signaling and pro-oncogenic cell cycle deregulation. 1,[12][13][14][15] Despite these recent advances, a better understanding of T-PLL pathobiology is of importance in order to identify novel treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we report the first known BRAF V600E mutation found in T‐PLL. Previous studies have shown recurrent mutations in the JAK/STAT pathway, ATM , genetic modifiers and DNA repair mechanisms; this BRAF V600E mutation likely represents an uncommon finding but more studies are required to identify other such mutations with potential therapeutic benefit 10‐15 . Our patient, having progressed through standard of care treatments, was trialled on novel treatments including dasatinib, venetoclax and vemurafenib.…”
Section: Figurementioning
confidence: 87%